Environmental microbiology - Pepper, Ian L.; Gerba, Charles P., 1945-; Gentry, Terry J. (Amsterdam : Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
"Designed for advanced undergraduate students, graduate students, and environmental professionals, this book builds upon the tremendous success of the previous editions with a comprehensive and up-to-date discussion of environmental microbiology as a discipline that has greatly expanded in scope and interest over the past several decades"--Page 4 of cover.
Introduction to environmental microbiology -- Microorganisms found in the environment -- Bacterial growth -- Earth environments -- Aeromicrobiology -- Aquatic environments -- Extreme environments -- Environmental sample collection and processing -- Microscopic techniques -- Cultural methods -- Physiological methods -- Immunological methods -- Nucleic acid-based methods of analysis -- Microbial source tracking -- Microbial transport in the subsurface -- Biogeochemical cycling -- Microorganisms and organic pollutants -- Microorganisms and metal pollutants -- Microbial diversity and interactions in natural ecosystems -- Microbial communication : bacteria/bacteria and bacteria/hose -- Bioinformation and 'omic approaches for characterization of environmental microorganisms -- Environmentally transmitted pathogens -- Indicator microorganisms -- Risk assessment -- Municipal wastewater treatment -- Land application of organic residuals : municipal biosolids and animal manures -- Recycled water treatment and reuse -- Drinking water treatment and distribution -- Disinfection -- Domestic and indoor microbiology -- Global emerging microbial issues in the Anthropocene Era.
pharmacy bookfair2016
Includes bibliographical references and index.
Keywords: Microbial ecology